Antibiotic resistance pattern and frequency of some beta lactamase genes in Klebsiella pneumoniae isolated from raw milk samples in Iran - ENFERAD, E.; MAHDAVI, S. (Journal of the Hellenic Veterinary Medical Society, 2021)
Klebsiella pneumoniae have become an important cause of mastitis in dairy cows. Resistance to beta lactam antibiotics resulted from beta lactamases enzyme production. The aim of this study was to investigate the antibiotic resistance pattern and frequency of some beta lactamase genes in Klebsiella pneumoniae isolated from raw milk samples in Iran. 200 raw cow milk samples were collected from different villages of north west of Iran. The samples were cultured and biochemical tests were performed for phenotypic diagnosis. Then, antibiotic resistance pattern was determined by antibiogram test. Finally, the presence of CTX, SHV and TEM genes in Klebsiella pneumoniae isolates was found by PCR method. Of total 200 raw cow milk samples, 80 samples (40%) contained Klebsiella pneumoniae. The frequency of CTX, SHV and TEM genes in Klebsiella pneumoniae isolates was 50 (62.5%), 34 (42.5%) and 70 (87.5%), respectively. 14 Klebsiella pneumoniae isolates (17.5%) possessed all three intended genes simultaneously. All strains of Klebsiella pneumoniae (100%) were resistant to ampicillin. The most strains were resistant to ceftriaxone (75%), gentamicin (70%) and nitrofurantoin (70%). 4 Klebsiella pneumoniae strains (5%) were resistant to all of tested antibiotics. The results showed high frequency of ESBLs and antibiotic resistance in Klebsiella pneumonia samples isolated from raw milk. It may occur exchange of resistance genes within and across species and with commensal bacteria of the human and animals.